The SALT and START Triage System for Classifying Patient Acuity Level: A Systematic Review - Purwadi, Hendri; Breaden, Katrina; McCloud, Christine; Pranata, Satriya (Nurse Media Journal of Nursing, 2021)
Background: Two common triage systems have been widely used in mass casualty incidents (MCIs) and disaster situations, namely START (simple triage algorithm and rapid treatment) and SALT (sort, assess, lifesaving, intervention, and treatment/transport). There is currently controversy regarding the effectiveness of SALT over the START triage system.Purpose: This systematic review aims to compare the accuracy of the SALT and START triage systems in disaster and MCI settings.Methods: The literature was searched using a systematic search strategy for articles published from 2009 to 2020 in the Medline, CINAHL, Web of Science, Scopus, PubMed, ProQuest databases, and the grey literature. This review included simulation-based and medical record-based studies investigating the accuracy and applicability of the SALT and START triage systems in adult and child populations during MCIs and disasters. All types of studies were included. The PRISMA flowchart was used to retain the articles, and the Joanna Briggs Institute critical appraisal tools were used to assess the quality of the reviewed studies.Results: Of 1,450 articles identified in the search, 10 articles were included. It was found that the START triage system had a wide range and inconsistent levels of accuracy (44% to 94.2%) compared to the SALT triage system (70% to 83%). The under-triage error of the START triage system ranged from 2.73% to 20%, which was slightly lower than the SALT triage system (7.6% to 23.3%). The over-triage error of the START triage system (2% to 53%) was slightly higher than the SALT triage system (2% to 22%). However, the time taken to apply START triage system (70 to 72.18 seconds) was faster than for the SALT triage system (78 seconds).Conclusion: The START triage system was simpler and faster than SALT. Conversely, the SALT triage system appeared to be slightly more accurate, more consistent, and had a lower rate of under- and over-triage error than START. It appears that neither the SALT nor the START triage system is superior to the other. Further research is needed to establish the most appropriate disaster and MCI triage system, especially for the Indonesian context.Â